Comparison of Group Eye Movement Desensitization and Reprocessing with Cognitive and Behavioral Therapy Protocol after the 2020 Earthquake in Turkey: A Field Study in Children and Adolescents - Karadağ, Mehmet; Karadeniz, Pınar Günel (European Journal of Therapeutics, 2021)
Objective: We aimed at comparing the efficiency of “Eye Movement Desensitization and Reprocessing Integrative Group Treatment Protocol (EMDR-IGTP)” with “Cognitive and Behavioral Therapy Based Crisis Prevention Program for Children and Adolescents (CIPCA)” in children who survived the 2020 earthquake in Turkey. Methods: We randomly divided 56 children and adolescents who were earthquake victims between the ages of 8 and 14 into two groups. Half of the participants underwent EMDR-IGTP, while the other underwent CIPCA. Outcomes were obtained using clinical global impression (CGI) and the subjective units of distress (SUDS) scales before and after therapy. Results: The median age of the participants was 10 years (range: 8–14) and 53.6% of them were male. The median CGI scores of the EMDR-IGTP group before and after therapy were 7 (3–7) and 1 (1–7), while that of the CIPCA group before and after therapy were 7 (3–7) and 4 (2–7), respectively (p<0.001). The median SUDS scores of the EMDR-IGTP group before and after therapy were 10 (5–10) and 1 (0–10), while that of the CIPCA group before and after therapy were 9 (5–10) and 5.5 (3–9), respectively (p<0.001). Conclusion: Both EMDR-IGTP and CIPCA are effective in reducing the acute traumatic stress following the earthquake; however, EMDR-IGTP is relatively more effective. Thus, both methods can be used as a psychosocial intervention in post-earthquake traumatic events.